The Poverty Impacts of Climate Change - Skoufias, Emmanuel; Rabassa, Mariano; Olivieri, Sergio; Brahmbhatt, Milan (World Bank, Washington, DC, 2012)
Over the last century, the world has seen a sustained decline in the proportion of people living in poverty. However, there is an increasing concern that climate change could slow or possibly even reverse poverty reduction progress. Given the complexities involved in analyzing climate change impacts on poverty, different approaches can be helpful; this note surveys the results of recent research on climate change impacts on poverty.